The Coworker - McFadden, Freida (Naperville, Illinois: Poisoned Pen Press, 2023)
"Dawn Schiff is strange. At least, everyone at work thinks so. She never says the right thing. She has no friends. And she is always at her desk at precisely 8:45 a.m. So when Dawn doesn't show up to the office one morning, her coworker Natalie Farrell-beautiful, popular, top sales rep five years running-is surprised. Then she receives an unsettling, anonymous phone call that changes everything... Now, Natalie is irrevocably tied to Dawn as she finds herself caught in a twisted game of cat and mouse that leaves her wondering: who's the real victim? But one thing is incredibly clear: somebody hated Dawn Schiff. Enough to kill."
Keywords: Thrillers (Fiction)